Korzó-pukhó : reacciones pasajeras al miedo : joyería simbólica (2017)
KORZâO-PUKHâO is an experience that invites the user to lead a life without fear proposing to accept what happens diary. It is natural to react emotionally, that is why I want to make these moments of fear evident, to normalize them and to be able to assimilate them calmly. It is made tangible through a glove that covers the forearm. It expresses different reactions to the fear when danger is perceived: the flight, the confrontation and the camouflage. In this way, the behavior of the piece helps to understand this emotion and its usefulness to evaluate the impacts of possibly dangerous actions, in itself and the environment. The objective of the project is to make evident the relation between body expressions and emotions. It also seeks that the user can assimilate the changes of his emotions and understand that these are involved in our decision making process since they influence our behavior by sending us messages of what we need to communicate or think. When we fear we ask for help, when we get angry, we ask for space. With sadness we seek support, disgust takes us away and joy reaffirms when something feels good. It seeks to impact the lifestyle of analytical and reflective people by offering them the opportunity to visualize their reactions to a danger in an obvious way so that they are more aware of how?, when? and why? Fear is generated in them. These people enjoy knowing each component of their personality and are not afraid to express their feelings or venture to face their fears.